2017
DOI: 10.1155/2017/9751756
|View full text |Cite
|
Sign up to set email alerts
|

IndustrialTransFatty Acid and Serum Cholesterol: The Allowable Dietary Level

Abstract: Trans fatty acid (TFA) from partially hydrogenated oil is regarded as the worst dietary fatty acid per gram due to its role in coronary heart disease. TFA consumption is decreasing worldwide, but some but not all observational studies indicate that TFA intake has little relevance to serum cholesterol levels in populations with low TFA intake (<1% E [percentage of total energy intake], Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
2
16
0
1
Order By: Relevance
“…However, some studies pointed out that the dose-response relations between TFA and lipid levels were not observed when the dietary intake of TFAs was low [9,28,29]. This is consistent with a TFA intervention study in young Japanese women, which showed no relationship between TFA and LDL-C or HDL-C [10]. The TRANSFAIR study, a cross-sectional study among middle-aged men and women in eight European countries, showed no associations between total TFA intake and LDL-C, HDL-C, or LDL-C/HDL-C ratio [30].…”
Section: Tablesupporting
confidence: 79%
See 2 more Smart Citations
“…However, some studies pointed out that the dose-response relations between TFA and lipid levels were not observed when the dietary intake of TFAs was low [9,28,29]. This is consistent with a TFA intervention study in young Japanese women, which showed no relationship between TFA and LDL-C or HDL-C [10]. The TRANSFAIR study, a cross-sectional study among middle-aged men and women in eight European countries, showed no associations between total TFA intake and LDL-C, HDL-C, or LDL-C/HDL-C ratio [30].…”
Section: Tablesupporting
confidence: 79%
“…Although it is likely that most of TFA are of dietary origin [10], we have very recently reported that various food intake except preference drinks such as tea or coffee, was not associated with plasma TFA levels in Japanese healthy old men [32]. A meta-analysis of seven cohorts with genome-wide association studies has not identified a significant genetic control for TFA, including palmitelaidc acids, trans-C18:1 isomers, trans/trans-C18:2, and trans/cis-C18:2 isomers [33].…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of TFA intake to decrease the risk of cardiovascular diseases in people is a major public health objective, and there are ongoing federal, state, and local activities to achieve this objective [9,10]. TFA exposure assessments to monitor the impact of these activities and their impact on lipid profiles are commonly performed using dietary questionnaires together with food composition databases to estimate intake, or through intervention studies [11]. However, little is known about lipid profiles and the actual TFA concentrations in human blood [12].…”
Section: Introductionmentioning
confidence: 99%
“…и аполипопротеина В100 (АпоВ100), а также увеличивают активность белка-переносчика эфиров ХС, отвечающего за перенос эфиров ХС с липопротеидов высокой плотности (ЛВП) на ЛНП. Это может частично объяснять механизм возникновения гиперлипидемии (преимущественно повышения уровня ХС-ЛНП и снижения уровня холестерина липопротеидов высокой плотности (ХС-ЛВП)) [8]. Ограничение потребления транс-жиров является ключевой мерой диетической профилактики сердечно-сосудистых заболеваний [1].…”
unclassified